The Impact of Investment Behaviour for Individual Welfare. (8th August 2013) - Post, Thomas; Gründl, Helmut; Schmit, Joan T.; Zimmer, Anja
<x xml:space="preserve">Abstract</x> The industrialized world has experienced a demographic shift that is straining public pension systems. Employer‐sponsored pension plans change from defined benefit to defined contribution. More emphasis is put on individually managed retirement funds. One concern with this movement is the potential negative effect on individual welfare if households' investment behaviour is suboptimal. Using micro‐level US data, we compare the optimal utility computed using a lifecycle model with the actual utility as reflected in empirical asset allocation choices. Average estimated welfare costs are below 3% of households' endowment (assets and human capital); yet specific population groups experience higher welfare costs.